EVALUATIONS OF SECONDARY METABOLITES ANTIOXIDANT AND ANTIMICROBIAL POTENTIAL IN LEAF EXTRACTS OF CORBICHONIA DECUMBENS (FORSSK.) EXELL - DHA, VIDYACHARANI; A, ARUNPRASATH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The present work is to evaluate the presence of phenol and flavonoid contents, 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) activity and antimicrobial activity of Corbichonia decumbens leaf extracts. Methods: C. decumbens leaves were collected, shaded, dried, powdered, and were subjected to Soxhlet apparatus for extraction using ethanol and petroleum ether. The ethanol and petroleum ether extract of the plant was tested for phenol, flavonoid, H2O2 contents, and DPPH scavenging activity using standard procedures. It is also subjected to antimicrobial activity against pathogenic bacteria and fungus using the well diffusion method. Results: The result revealed that the leaf extracts contain phenol, flavonoid, and H2O2 contents. The values of DPPH radical scavenging activity recorded for ethanol and petroleum ether extract were 55.90±0.10 and 41.23±0.20, respectively. Antimicrobial activities of ethanolic leaf extracts showed lesser values compared to standard values. Conclusion: The result of this study showed the presence of phenol and flavonoid content, evidenced the potential antioxidant and antimicrobial activity against all tested micro-organisms.